Komunikasi Internal Perusahaan di Masa Pandemi COVID-19 - Wulan Muhariani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The Stakeholders in the company cannot be separated from internal and external parties, so that corporate communication or organizational communication needs to be carried out by targeting both. This internal communication is a challenge in the company's activities, especially during the COVID-19 pandemic. As we know that the pandemic period is times that are beyond expectations, many policies and information from the company are up-to-date and need to be understood by the company's internal parties. Therefore, researchers want to see how the company's internal communication activities during the COVID-19 pandemic, especially the government's policy regarding Work From Home (WFH) in order to suppress the spread of the COVID-19 virus. The researcher used a qualitative approach in this study with case study research methods. From the results of the study, it was found that every company needs to communicate to internal parties, namely employees and stakeholders in it so that internal parties know the condition of the company, can work in line with company goals and can do what is expected by the company.